Efficient lithium-metal battery based on a graphene oxide-modified heat-resistant gel polymer electrolyte with superior cycling stability and excellent rate capability. Issue 2 (14th December 2021) - Wang, Xiaoxiao; Zhao, Huijuan; Deng, Nanping; Li, Yanan; Yu, Ruru; Wen, Yajie; Kang, Weimin; Cheng, Bowen
Abstract : Fabrication of a PMIA fiber separator for lithium-ion batteries. Abstract : Lithium-metal batteries have revived increasing attention and research on account of the growing demands for high-energy electrical energy storage, but their unsatisfactory cycling stability and service safety have greatly limited their rapid development. In this study, a heat-resistant gel polymer electrolyte (GPE) based on a poly(vinylidene fluoridehexafluoropropylene) (PVDF-HFP)/poly- m -phenyleneisoph-thalamide (PMIA) nanofiber membrane doped with graphene oxide (GO) nanosheets was fabricated via a one-step electrospinning method. Significantly, the as-prepared heat-resistant gel PMIA separator with the assistance of GO sheets was endowed with a relatively low fiber diameter and large specific surface area, bringing about a markedly enhanced liquid electrolyte wettability and absorptivity so as to improve lithium-ions conduction and interfacial compatibility. Meanwhile, the obtained heat-resistant GO-modified GPE exhibited excellent heat resistance and strengthened mechanical strength, which in turn set a solid foundation for ensuring high security. Consequently, an assembled lithium-metal cell using the heat-resistant gel PMIA separator delivered a noticeable improvement in cycling stability with a capacity retention rate of 84.7% (0.077% capacity fading per cycle) after 200 cycles at 0.5C, accompanied by excellent rate performance with a high capacity recovery efficiency of 97.9%. This work shares a convenient strategy for the synthesis of a dual-functional and stable superstructure separator for advanced Li-ion batteries.